Fast, Air‐Stable Infrared Photodetectors based on Spray‐Deposited Aqueous HgTe Quantum Dots. (20th June 2013) - Chen, Mengyu; Yu, Hui; Kershaw, Stephen V.; Xu, Haihua; Gupta, Shuchi; Hetsch, Frederik; Rogach, Andrey L.; Zhao, Ni
<x xml:space="preserve">Abstract</x> The ability to detect near‐infrared and mid‐infrared radiation has spawned great interest in colloidal HgTe quantum dots (QDs). In contrast to the studies focused on extending the spectral range of HgTe QD devices, the temporal response, another figure of merit for photodetectors, is rarely investigated. In this work, a single layer, aqueous HgTe QD based photoconductor structure with very fast temporal response (up to 1 MHz 3 dB bandwidth) is demonstrated. The device is fabricated using a simple spray‐coating process and shows excellent stability in ambient conditions. The origin of the remarkably fast time response is investigated by combining light intensity‐dependent transient photocurrent, temperature‐dependent photocurrent, and field‐effect transistor (FET) measurements. The charge carrier mobility, as well as the energy levels and carrier lifetimes associated with the trap states in the QDs, are identified. The results suggest that the temporal response is dominated by a fast bimolecular recombination process under high light intensity and by a trap‐mediated recombination process at low light intensity. Interestingly, it was found that the gain and time response of aqueous HgTe QD‐based photoconductors can be tuned by controlling the QD size and surface chemistry, which provides a versatile approach to optimize the photodetectors with selectable sensitivity and operation bandwidth.